Basilar artery dissection: A rare complication of posterior fossa epidermoid cyst resection, and evaluation of the possible effects of cerebrospinal fluid drainage on disease progression. (October 2016) - Pikis, Stylianos; Cohen, José E.; Margolin, Emil
Highlights: Basilar artery dissecting aneurysm complicating craniotomy for tumor resection has been rarely described. The pathophysiology of intracranial arterial dissecting aneurysms is unclear. Hydrocephalus and CSF drainage may have an effect on progression of intracranial arterial dissection. Abstract: We report a rare case of a 45-year-old female with an unruptured basilar artery dissecting aneurysm presenting with locked-in syndrome due to brainstem ischemia eleven months following resection of a giant cerebellopontine angle epidermoid cyst and three months after insertion of ventriculo peritoneal shunt due to hydrocephalus. The etiology of basilar artery dissection and the effect of hydrocephalus and ventricular cerebrospinal fluid drainage on disease progression in this patient are unclear. Our report suggests a possible effect of hydrocephalus and ventricular cerebrospinal fluid drainage on intracranial arterial dissection progression.